A Compact Planar Four-port MIMO Antenna for 28/38 GHz Millimeter-wave 5G Applications - Tadesse, A. D.; Acharya, O. P.; Sahu, S. (Advanced electromagnetics, 2022)
This article presents a planar four-port microstrip line-fed Multiple-Input Multiple-Output (MIMO) antenna operating at 5G millimeter-wave candidate bands of 28 GHz and 38 GHz. A rectangular-shaped patch antenna is designed as a main radiator to obtain a resonance at 28 GHz. Etching of a single-element split-ring resonator (SRR) metamaterial unit cell from the basic patch radiator introduces an additional resonance band at 38 GHz. The suggested MIMO antenna is built on Rogers RT5880 substrate material with a dimension of 14 mm × 14 mm, a thickness of 0.8 mm, and a relative permittivity of 2.2.The measured results show that the antenna achieves bandwidths of 26.6-29 GHz and 37.3-39.3 GHz, whereas greater than 25 dB of port isolation between antenna elements over both bands is obtained without applying any complex decoupling structure. The antenna’s equivalent circuit diagram is presented with the help of lumped elements to characterize its electrical responses. The investigated diversity performance parameters, which result in an envelope correlation coefficient below 0.005, diversity gain of almost 10 dB, and channel capacity loss of less than 0.35 bits/s/Hz, are all found within their conventional limits. The findings show the viability of the design for millimeter-wave 5G applications.